INTERNATIONAL ORGANIZATIONS PROTECTING CHILD RIGHTS - E. Tursunaliyeva; N. Qayumjonova; M. Ibrahimova (Web of Journals Publishing, 2024)
In many countries of the world, protection of children's rights is one of the priorities of the country's legislation. But the role of international organizations in protecting children's rights is incomparable. In this article, international organizations that protect children's rights are briefly discussed.
Keywords: child, law, child rights, protection, legislation, organization, international.